Mediating effects of user experience usability: An empirical study on mobile library application in China. Issue 5 (1st October 2018) - Ke, Ping; Su, Fu
Abstract : Purpose: This study aims to explore whether the usability of user experience for mobile library application plays a mediating role in the relation between the success factors of information systems and net benefit. Design/methodology/approach: The theoretical model of "information system success factor–user experience usability–net benefit" was constructed. A questionnaire was conducted at the Nankai University. The mediating effects of the usability of the mobile library application on information system success factors and net benefit were examined using hierarchical linear regression and structural equations. Findings: First, the usability of user experiences is positively correlated to information quality, system quality and service quality. Second, user experience usability has a significant mediating effect on the relation between information system success factors and net benefit. Originality/value: This study improves upon the DeLone and McLean model, connects the usability of user experience with the model and constructs the success factor mechanism of the mobile library application. It provides a theoretical basis for interpreting the relation between the mobile library application and users.